PERSEBARAN BARU NICANDRA PHYSALODES (L.) GAERTN DI PULAU JAWA - Ana Widiana; Rahmat Agung Munggaran; Putri Leony Puspita Sari; Muhammad Efendi (LP4MK STKIP PGRI Lubuklinggau, 2022)
Nicandra physalodes belongs to the Solanaceae family that introduce from Peru as an ornamental plant for long ago. This species was naturalized in Java, particularly in Dieng Plateau Central Java and Malang East Java. Furthermore, N. physalodes has been identified as a host of tomato severe rugose virus (ToSRV) in Brazil and as an invasive species in Indonesia. Botanical information and ecological data of this species are still limited knowns, although it has long been discovered in Java. Therefore, the study aims to update the morphological data and range distribution of N. physalodes in West Java. Samples were conducted from vegetable gardens in Pangkalan Village, Ciwidey, Bandung West Java. Morphology data were observed based on living material collected in the field and identified using Flora of Java Book. The distribution data were obtained using a field survey, herbarium observations, and a literature review. Morphologically, the specimens collected from Ciwidey weresimilar to the description in Flora of Java. Seed morphology and stomata data were added to the morphological description of N. physalodes. New distribution in Ciwidey add extends the range of this species outside of its origin area in Java.